Production of Chinese Medicinal Herbs in North America: Challenge and Reconciliation - Jean Giblette (Chinese Medicine and Culture)
As the practice of traditional Chinese medicine developed in the United States since the 1970s, evidence has accumulated suggesting that an undetermined number of the herbs of the Chinese Materia Medica could be produced in North America. While some attempts have been made to establish production, growers are inhibited by lack of access to capital and technical support. The evidence in support of US domestic production – including (1) historical, (2) sociological, (3) ecological, and (4) agronomic factors – is reviewed. Economic obstacles to this type of production are described, as directly experienced by the farmers, Chinese herbal medicine practitioners, and organizers involved. When analyzed in reference to current trends, however, these economic obstacles appear, at least potentially, as temporary. Because popular demand supported the rise of traditional Chinese medicine practice and the growth of organic food production, these social movements could expand and promote conditions that favor domestic production of Chinese herbs.